Penerapan Pendekatan Saintifik dalam Model Jigsaw untuk Meningkatkan Keaktifan Belajar Siswa Kelas X IPS - Amelia Putri; Maskun Maskun; Yustina Sri Ekwandari (FKIP UNIVERSITAS LAMPUNG, 2018)
The purpose of this study is to determine whether or not the increase in student learning activity after using the scientific approach in the Jigsaw Model on the Subject History of class X IPS students in SMA Negeri 1 Tulang Bawang Tengah Year 2017/2018